University Actions for Entrepreneurial Development: a Comparative Analysis: Un análisis comparativo (Ciencias Económicas, 2024)
For several decades, universities have carried out various activities aimed at promotingthe entrepreneurial development of their students in a complex, volatile context, with agrowing technological and digital impact on the world of work. Consequently, entrepreneurial education has gradually become a specific discipline. Within this framework, this work has two main objectives: to delve into the main characteristics of entrepreneurial education, the design and contents of the usual academic offerings and the profiles required for participating teaching staff; and to carry out a comparative analysis of the activities within this field Argentinian public and private universities are involved in. The data collected revealed the lack of impact measurement as the greatest weakness of the actions undertaken.
Keywords: Entrepreneurial education; Entrepreneurship; Entrepreneurial university